Człowiek każdy, jako fenomen "czterdzieści i cztery". Przegląd interpretacji = Every man as a phenomenon of "forty and four". Review of interpretation - Saja, Krystian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article aims to review the concept of reading the words "forty and four" from Adam Mickiewicz`s drama "Dziady" (Part III) and to present a new author`s interpretation that makes reference to the history of the Napoleon Bonaparte family. We will follow the links of the "Widzenie ks. Piotra" with Napoleon I, Napoleon II and Ludwik Napoleon Bonaparte. Mickiewicz`s unwavering faith in the strength of this French line of monarchs will also be analysed.
Keywords: dramat romantyczny; Mickiewicz, Adam (1798-1855); Napoleon Bonaparte (cesarz Francuzów; 1769-1821); przedmiot mentalny; interpretacja; romantic drama; mental object; interpretation